2021
DOI: 10.3390/ijms22041891
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk of Toll-Like Receptor 5 and Mu-Opioid Receptor Attenuates Chronic Constriction Injury-Induced Mechanical Hyperalgesia through a Protein Kinase C Alpha-Dependent Signaling

Abstract: Recently, Toll-like receptors (TLRs), a family of pattern recognition receptors, are reported as potential modulators for neuropathic pain; however, the desired mechanism is still unexplained. Here, we operated on the sciatic nerve to establish a pre-clinical rodent model of chronic constriction injury (CCI) in Sprague-Dawley rats, which were assigned into CCI and Decompression groups randomly. In Decompression group, the rats were performed with nerve decompression at post-operative week 4. Mechanical hyperal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In this contest, it has been demonstrated that opioids are TLR4 agonists (Zhang and others 2020b) and an increased IL-1β production has been observed after PBMC stimulation with TLR2 and TLR4 agonists (Kwok and others 2012). These data could be explained and enhanced considering a recent finding (Chang and others 2021), which describes the cross-talk of TLRs and MOR in a preclinical rodent model of chronic constriction injury (CCI). Here the authors suggested that mechanical hyperalgesia might be the result of the cross-talk between TLRs and MOR in a PKCα-dependent manner, opening the way for novel neuropathic pain therapeutic strategies (Table 2).…”
Section: Immune Cells and Opioid Treatmentmentioning
confidence: 91%
See 1 more Smart Citation
“…In this contest, it has been demonstrated that opioids are TLR4 agonists (Zhang and others 2020b) and an increased IL-1β production has been observed after PBMC stimulation with TLR2 and TLR4 agonists (Kwok and others 2012). These data could be explained and enhanced considering a recent finding (Chang and others 2021), which describes the cross-talk of TLRs and MOR in a preclinical rodent model of chronic constriction injury (CCI). Here the authors suggested that mechanical hyperalgesia might be the result of the cross-talk between TLRs and MOR in a PKCα-dependent manner, opening the way for novel neuropathic pain therapeutic strategies (Table 2).…”
Section: Immune Cells and Opioid Treatmentmentioning
confidence: 91%
“…Mast cell have been shown to increase in human inflammatory diseases (Nigrovic and Lee 2005), and in murine models, which lack mast cells, a reduction of pain can be observed (Milenkovic and others 2007). Blocking histamine signaling by using histamine receptor antagonists reduces mechanical and thermal hyperalgesia (Gupta and Harvima 2018;Liu and others 2021). Mast cells express opioid receptors in their surface but the mechanism that describe the communication between these cells and peripheral nerves in pain pathways is still unknown.…”
Section: Immune Cells and Opioid Treatmentmentioning
confidence: 99%
“…The scientific contributions enclosed in the Special Issue "The Multiple Mechanisms Underlying Neuropathic Pain" reflect the complexity of the current scenario by providing compelling examples of the different approaches to the investigation of mechanisms and the development of potential therapies for the control of NeuP. In this regard, emblematic are the two papers by Chang C. et al and Basu P. and colleagues entitled "Cross-Talk of Toll-Like Receptor 5 and Mu-Opioid Receptor Attenuates Chronic Constriction Injury-Induced Mechanical Hyperalgesia through a Protein Kinase C Alpha-Dependent Signaling" [4] and "Effects of Curcumin and Its Different Formulations in Preclinical and Clinical Studies of Peripheral Neuropathic and Postoperative Pain: A Comprehensive Review" [5], respectively. The first paper is a scientific investigation that analyzes the molecular underpinnings of the cross-talk between member 5 of the toll-like receptors (TLR5) and the mu-opioid receptor (MOR) that was found to be implicated in the process of nerve decompression following chronic constriction injury (CCI) of the sciatic nerve.…”
mentioning
confidence: 99%
“…As a matter of fact, and despite the small size of the sample of patients screened or the lack of control for medications, this work by Thoma and coworkers [3] is an interesting explorative study that provides evidence that an alteration related to the habituation to nBR can be used as a diagnostic marker of defective pain processing and CRPS. The first edition of the SI, "The Multiple Mechanisms Underlying Neuropathic Pain", featured a study focused on the crosstalk between Toll-like receptor 5 and mu-opioid receptors (MORs) as functional interaction-mediating NeP-induced hyperalgesia [7]. Interestingly, the issue concerning opioid-mediated signaling as an anti-inflammatory strategy is discussed again through an experimental model of NeP (i.e., chronic constriction injury (CCI) in the work conducted by Vicario and colleagues [8].…”
mentioning
confidence: 99%